2019
DOI: 10.3390/ma12091419
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Property Relationships in Shape Memory Metallic Glass Composites

Abstract: Metallic glass composites with shape memory crystals show enhanced plasticity and work-hardening capability. We investigate the influence of various critical structural aspects such as, the density of crystalline precipitates, their distribution and size, and the structural features and intrinsic properties of the phase on the deformation behavior of metallic amorphous Cu 64 Zr 36 composites with B2 CuZr inclusions using molecular dynamics simulations. We find that a low density of small B2 incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 42 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…Recently, understanding the structural heterogeneity of MGs and its relation to the intrinsic properties is an area of interest for researchers [ 9 ]. Intensive studies focused on the relationships between the structural heterogeneity of MGs and superplasticity [ 10 , 11 ], thermal expansion [ 12 ], magnetoelastic effect [ 13 ], catalytic performance for dye degradation [ 14 ], electrochemical supercapacitors [ 15 ], and hydrogen generation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, understanding the structural heterogeneity of MGs and its relation to the intrinsic properties is an area of interest for researchers [ 9 ]. Intensive studies focused on the relationships between the structural heterogeneity of MGs and superplasticity [ 10 , 11 ], thermal expansion [ 12 ], magnetoelastic effect [ 13 ], catalytic performance for dye degradation [ 14 ], electrochemical supercapacitors [ 15 ], and hydrogen generation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A former study reports that the ductility of BMGs intrinsically correlates with their STZs volumes 18 . This explains why an improved deformability/ductility of MGs was observed after imprinting, minor alloying, flash annealing, integrating crystalline phases to form composites or deformationcycling in the so-called elastic regime [3][4][5][6][7][8][9][10][37][38][39] since all these procedures stimulate topological changes by shuffling atoms/clusters and thus increase the STZ volume. The results obtained from Fig.…”
Section: Modelsmentioning
confidence: 99%
“…Atomistic models as a useful supplement can provide some important information for the understanding complex microstructure evolution characteristics during nanoindentation; especially they have the indisputable advantage of characterizing the dislocation movement in crystalline materials [ 17 , 18 , 19 , 20 ] and shear bands (SB) in single-phase MGs [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ], respectively. Incorporating crystalline phases mitigates the poor failure resistance in MGs, which accommodates plastic strain by dislocation slip, effectively preventing shear band propagation [ 4 , 5 , 6 , 27 , 28 , 29 ]. More recent simulation studies have confirmed that the crystalline phase inserted into the amorphous phase can impede the propagation of SBs, and plays a vital role in the plastic deformation mechanism of ACNLs [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%